PENGARUH TERPAAN KAMPANYE #IMPERFECTBEAUTY TERHADAP SIKAP KHALAYAK PADA KONSEP KEPERCAYAAN DIRI - Zahirah, Yasmina (The Commercium, 2023)
The stigma of the standard of beauty in society says that beautiful is the one who has white skin, but it turns out that it is not in accordance with Indonesian society, the majority of which have brown skin. The media indirectly creates the concept of an ideal body which is constructed into a social reality by some people and makes women dissatisfied with the condition of their bodies and hopes to look like the women shown in the media. If he or someone else does not meet the standards of beauty, he will be discriminated against. This study aims to determine whether there is an effect of exposure to the #ImPerfectBeauty campaign on audience attitudes in the concept of self-confidence, using explanatory quantitative research methods. Data was collected using a questionnaire instrument in the form of a Google form which was distributed to audiences affected by the #ImPerfectBeauty campaign via Instagram @elsheskin. The results of this study indicate that the alternative hypothesis can be accepted with tcount (3.406) > ttable (1966). This means that exposure to the #ImPerfectBeauty campaign has had an impact on shaping audience attitudes towards the concept of self-confidence.